Isolation of Catchin and Epigallocatchin From Iraqi Rhus coriaria By Preparative High-Performance Liquid Chromatography (PHPLC) - Nabaa Mohammed Ibrahem; Enas Jawad Khadum; Shihab Hattab Mutlag (College of Pharmacy University of Baghdad, 2022)
ABSTRACT Two compounds were isolated from the fruit part of Rhus coriaria that grow wildly or cultivated in the north of Iraq. The compounds were separated by preparative high-Performance Liquid Chromatography and their structures were established based on detailed spectroscopic techniques like FTIR and LC-MS/MS. Keywords: Rhus coriaria, Preparative HPLC, LC-MSMS, FTIR